A phase 2 trial of long-acting TransCon growth hormone in adult GH deficiency. Issue 3 (April 2017) - Höybye, Charlotte; Pfeiffer, Andreas F H; Ferone, Diego; Christiansen, Jens Sandahl; Gilfoyle, David; Christoffersen, Eva Dam; Mortensen, Eva; Leff, Jonathan A; Beckert, Michael
Abstract : TransCon growth hormone is a sustained-release human growth hormone prodrug under development in which unmodified growth hormone is transiently linked to a carrier molecule. It is intended as an alternative to daily growth hormone in the treatment of growth hormone deficiency. This was a multi-center, randomized, open-label, active-controlled trial designed to compare the safety (including tolerability and immunogenicity), pharmacokinetics and pharmacodynamics of three doses of weekly TransCon GH to daily growth hormone (Omnitrope). Thirty-seven adult males and females diagnosed with adult growth hormone deficiency and stable on growth hormone replacement therapy for at least 3 months were, following a wash-out period, randomized (regardless of their pre-study dose) to one of three TransCon GH doses (0.02, 0.04 and 0.08 mg GH/kg/week) or Omnitrope 0.04 mg GH/kg/week (divided into 7 equal daily doses) for 4 weeks. Main outcomes evaluated were adverse events, immunogenicity and growth hormone and insulin-like growth factor 1 levels. TransCon GH was well tolerated; fatigue and headache were the most frequent drug-related adverse events and reported in all groups. No lipoatrophy or nodule formation was reported. No anti-growth hormone-binding antibodies were detected. TransCon GH demonstrated a linear, dose-dependent increase in growth hormone exposure without accumulation. Growth hormone maximum serum concentration and insulin-like growth factor 1 exposure were similar after TransCon GH or Omnitrope administered at comparable doses. The results suggest that long-acting TransCon GH has a profile similar to daily growth hormone but with a more convenient dosing regimen. These findings support further TransCon GH development.